Omega‐3 fatty acid supplementation in pregnancy—baseline omega‐3 status and early preterm birth: exploratory analysis of a randomised controlled trial. (3rd March 2020) - Simmonds, LA; Sullivan, TR; Skubisz, M; Middleton, PF; Best, KP; Yelland, LN; Quinlivan, J; Zhou, SJ; Liu, G; McPhee, AJ; Gibson, RA; Makrides, M
Abstract : Objective: To identify a polyunsaturated fatty acid (PUFA) biomarker able to detect which women with singleton pregnancies are most likely to benefit from omega‐3 supplementation to reduce their risk of early preterm birth. Design: Exploratory analysis of a randomised controlled trial. Setting: Six Australian hospitals. Population: Women with a singleton pregnancy enrolled in the ORIP trial. Methods: Using maternal capillary whole blood collected ~14 weeks' gestation, the fatty acids in total blood lipids were quantified using gas chromatography. Interaction tests examined whether baseline PUFA status modified the effect of omega‐3 supplementation on birth outcomes. Main outcome measure: Early preterm birth (<34 weeks' gestation). Results: A low total omega‐3 PUFA status in early pregnancy was associated with a higher risk of early preterm birth. Among women with a total omega‐3 status ≤4.1% of total fatty acids, omega‐3 supplementation substantially reduced the risk of early preterm birth compared with control (0.73 versus 3.16%; relative risk = 0.23, 95% confidence interval [CI] 0.07–0.79). Conversely, women with higher total omega‐3 status in early pregnancy were at lower risk of early preterm birth. Supplementing women with a baseline status above 4.9% increased early preterm birth (2.20 versus 0.97%; relative risk = 2.27, 95% CI 1.13–4.58). Conclusions: Women with singleton pregnancies and low total omega‐3 PUFA status early in pregnancy have an increased risk of early preterm birth and are most likely to benefit from omega‐3 supplementation to reduce this risk. Women with higher total omega‐3 status are at lower risk and additional omega‐3 supplementation may increase their risk. Tweetable abstract: Low total omega‐3 fat status helps identify which women benefit from extra omega‐3 to reduce early prematurity. Tweetable Abstract: Low total omega‐3 fat status helps identify which women benefit from extra omega‐3 to reduce early prematurity.